2012
DOI: 10.1103/physrevlett.108.228302
|View full text |Cite
|
Sign up to set email alerts
|

Orientational Order and Alignment of Elongated Particles Induced by Shear

Abstract: Shear induced alignment of elongated particles is studied experimentally and numerically. We show that shear alignment of ensembles of macroscopic particles is comparable even on a quantitative level to simple molecular systems, despite the completely different types of particle interactions. We demonstrate that for dry elongated grains the preferred orientation forms a small angle with the streamlines, independent of shear rate across three decades. For a given particle shape, this angle decreases with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
133
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(170 citation statements)
references
References 44 publications
35
133
2
Order By: Relevance
“…Due to dynamics in continuous shearing, this ordering phenomenon emerges even in systems composed of particles with very low platyness with a shape differing only slightly from spherical shape. This kind of ordering has previously been observed in experiments [27,22] and numerical simulations mainly with two-dimensional elongated particles [28,15,18]. Regarding the privileged direction of alignment, we found that, as platyness increases, this direction gradually changes from that of the major principal stress to a direction that is perpendicular to the shear direction.…”
Section: Summary and Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Due to dynamics in continuous shearing, this ordering phenomenon emerges even in systems composed of particles with very low platyness with a shape differing only slightly from spherical shape. This kind of ordering has previously been observed in experiments [27,22] and numerical simulations mainly with two-dimensional elongated particles [28,15,18]. Regarding the privileged direction of alignment, we found that, as platyness increases, this direction gradually changes from that of the major principal stress to a direction that is perpendicular to the shear direction.…”
Section: Summary and Discussionsupporting
confidence: 48%
“…This evolution of the privileged direction of alignment is consistent with several observations reported in Refs. [28,27,22].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several common methods used to characterize grain ensembles, irrespective of grain shapes. Modern experimental tools like X-ray Computed Tomography (X-ray CT) or Magnetic Resonance Imaging (MRI) are increasingly used for characterizing not only coarse grain packing [24][25][26], but also local packing structures and orientation at the grain level [27][28][29]. Grain sizes accessible with X-ray CT equipment range from several micrometers [30] to centimeters [28].…”
Section: B Characterization Methods and Modelingmentioning
confidence: 99%
“…Three-dimensional experiments require either the use of invasive observation methods (excavation) or tomographic tools. Extensive quantitative experimental characterizations of the reorientation of elongated particles under shear in a 3D geometry were recently performed by means of optical imaging and X-ray CT [28,29,128]. Grains with different aspect ratios and geometrical shapes were sheared in a cylindrical split-bottom container (Fig.…”
Section: Sheared Grainsmentioning
confidence: 99%